Biopsychosocial Factors Associated with Preterm Birth at Dr. Moewardi Hospital, Surakarta, Central Java - Bachtiar, Harrys; Budihastuti, Uki Retno; Salimo, Harsono (Journal of Maternal and Child Health, 2018)
Background: Preterm birth has been defined asgestational age of birth between 28 and 37 weeks. Prematurity is a major public health issue as studies have shown it increases the risk of mortality and morbidity of the newborns. The purpose of this study was to examine biopsychosocial factors associated with preterm birth.Subjects and Method: This was an analytic observational with a case control design. The study was carried out at Dr. Moewardi Hospital, Surakarta, Central Java, from April to May 2018. A total sample of 200 of the newborn infants was selected for this study by fixed disease sampling, composing of 100 preterm newborns and 100 term newborns. The dependent variable was prematurity. The independent variables were maternal age, nutritional status, parity, ambient smoke exposure, maternal education, family income, and family support. The data on prematurity was obtained from medical record. The other variables were measured by a set of questionnaire. The data were analyzed by path analysis.Results: Preterm birth was positively associated with maternal age <20 or ?35 years (b= 1.58; CI 95%= 0.65 to 2.50; p<0.001), ambient smoke exposure (b= 1.42; CI 95%= 0.41 to 2.44; p=0.006), and parity (b= 1.77; CI 95%= 0.87 to 2.67; p<0.001). Preterm birth was negatively associated with good maternal nutritional status (b= 2.00; CI 95%= 2.92 to 1.08; p<0.001). Good maternal nutritional status was positively associated with strong family support (b= 0.93; CI 95%= 0.24 to 1.61; p=0.008), high family income (b= 2.26; CI 95%= 1.57 to 2.95; p<0.001), and high maternal education (b= 2.45; CI 95%= 1.76 to 3.17; p<0.001).Conclusion: Preterm birth is positively associated with maternal age <20 or ?35 years, ambient smoke exposure, and parity, but negatively associated with good maternal nutritional status.Keywords: preterm birth, biopsychosocial factors, path analysisCorrespondence:Harrys Bachtiar. Masters Program in Public Health, Universitas Sebelas Maret, Surakarta, Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java. Email: harrysbachtiar@gmail.com. Mobile: +6285257311700.Journal of maternal and child health (2018), 3(2): 138-145https://doi.org/10.26911/thejmch.2018.03.02.06